Systematic Literature Review : Knowledge Management sebagai pilar dalam Implementasi Corporate University - Utami, Teja (Cendekia Niaga, 2024)
This research produces an understanding of the importance of knowledge management in the development and implementation of corporate university (CorpU) in an organization. This research uses a systematic literature review method, consisting of identifying, classifying, reviewing, evaluating the results of previous researches that have been published on Google Scholar and Scopus. The research result shows that knowledge management and CorpU development and implementation cannot be separated. CorpU is developed to create a learning organization, of course it needs to be driven by individuals who learn continuously (learning culture). Knowledge management is very important to manege and facilitate individuals learning. Knowledge management trough a knowledge management system (KMS) provides to collect knowledge assets, manage and organize them, disseminate knowledge, use and develop knowledge, to save knowledge assets and realize to development sustainable innovation.